Timing matters: disentangling the neurocognitive sequence of mentalizing. Issue 11 (November 2022) - Rothmaler, Katrin; Berger, Philipp; Wiesmann, Charlotte Grosse
Abstract : A recent electrocorticographic study by Tan et al . makes an important contribution to understanding the processes involved in mentalizing by adding the temporal dimension to the brain network of mentalizing. Combined with multivariate methods, this approach has the potential to unveil the precise representations underlying mentalizing and their functional interplay.